Brusatol inhibits the invasion and migration of pancreatic cancer cells by suppressing the NRF2/NF-κB/STAT3 signal cascade. (May 2022) - Xiang, Yukai; Dai, Shengjie; Li, Ding; Zhu, Xiandong; Su, Jiadong; Chen, Bicheng; Wu, Minmin
Graphical abstract: Highlights: Pancreatic cancer-and immune-related pathways are enriched in tumors with high NFE2L2 expression. Brusatol could inhibit invasion and migration of pancreatic cancer cells. Reduced NRF2 expression results in suppressed invasion and migration of pancreatic cancer cells via the NF-κB/STAT3 pathway. Brusatol could reverse gemcitabine-induced activation of the NF-κB/STAT3 pathway. Abstract: The previous study has established that brusatol exhibits growth inhibitory and pro-apoptotic effects. However, whether brusatol can suppress the invasion and migration of pancreatic cancer cells remains unclear. Information in The Cancer Genome Atlas database indicates that NRF2 expression is tightly associated with the status of lymphatic metastasis and overall survival. Gene set enrichment analysis has also revealed that the JAK-STAT pathway could be suppressed by brusatol and is significantly enriched for phenotypes associated with high expression of the NRF2 gene. Therefore, we speculated and confirmed that brusatol can inhibit cell invasion and migration via the NRF2 pathway. Additionally, low NRF2 gene expression results in a function similar to that of brusatol as well as decreased expression of NF-κB and p-STAT3. Furthermore, brusatol reversed gemcitabine-induced overexpression of NF-κB and p-STAT3. Together, our results suggest that brusatol can inhibit the invasion and migration of pancreatic cancer cells through NRF2/NF-κB/STAT3 signaling cascade.